Neuromuscular control and coordination during cycling - Li, L. (Research Quarterly for Exercise and Sport, 2004)
The neuromuscular control aspect of cycling has been investigated through the effects of modifying posture and cadence. These studies show that changing posture has a more profound influence on neuromuscular coordination than does changing slope. Most of the changes with standing posture occur late in the downstroke: increased ankle and knee joint moment, reduced hip joint moment and greater activity in specific muscles. Due to the influence of lower extremity inertial properties, higher pedaling frequency induces more neuromuscular changes at the hip than at the knee or ankle joints. These neuromuscular adaptations to environmental and task constraints are discussed with regard to the contributions of the central nervous system and the solution provided by peripheral anatomical structure—mono- and biarticular muscles. The results indicate that training and related movement analysis should be specific to the motion, supporting the notion of task-specific training.